2020
DOI: 10.1111/ggi.14092
|View full text |Cite
|
Sign up to set email alerts
|

Association between frailty and changes in lifestyle and physical or psychological conditions among older adults affected by the coronavirus disease 2019 countermeasures in Japan

Abstract: Aim This study aimed to clarify the association between frailty and changes in lifestyle and physical or psychological conditions among community‐dwelling older adults affected by the coronavirus disease 2019 countermeasures in Japan. Methods This cross‐sectional study was carried out between 8 May and 12 June 2020 in Japan. Self‐reported questionnaires were distributed among 1353 older adults. To assess frailty, we used the frailty screening index. To assess changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…The influence of quarantine (and not disease) on the biological age of the respondents was noted by a number of researchers. In Japan, an increase in biological age, as determined by the Fragility Screening Index (FSI), was revealed in uninfected older people affected by COVID-19 restriction measures [ 50 ]. Our study demonstrated that in Russia during the quarantine period, there was a significant growth of biological age only in the group of working men; in the group of working women the increase in biological age was only at the tendency level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of quarantine (and not disease) on the biological age of the respondents was noted by a number of researchers. In Japan, an increase in biological age, as determined by the Fragility Screening Index (FSI), was revealed in uninfected older people affected by COVID-19 restriction measures [ 50 ]. Our study demonstrated that in Russia during the quarantine period, there was a significant growth of biological age only in the group of working men; in the group of working women the increase in biological age was only at the tendency level.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were 856 uninfected seniors affected by COVID-19 restrictions. The study showed that the introduction of quarantine resulted in a subjective decrease of daily movements, leg muscle strength, and food intake and in general resulted in an increase of the Fragility Index [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we could not measure physical exercise behaviors using accelerometers or pedometers, they were assessed using a simple questionnaire rather than a validated index. Although the validity of such surveys is not well established, face-to-face diagnosis during the COVID-19 pandemic is difficult, and hence, questionnaire surveys are used because of their simplicity and ease of classification [ 41 ]. Finally, the effects of other unmeasured confounding factors, such as cognitive function, were not tested.…”
Section: Discussionmentioning
confidence: 99%
“…Items about worry or anxiety were scored as decreased = 1, slightly decreased = 2, unchanged = 3, slightly increased = 4, increased = 5. Almost all items of QCL related to frailty status have been validated previously ( Shinohara et al, 2021a ; Shinohara et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%